MENGUATKAN INDONESIA: REVITALISASI PEMBELAJARAN PENDIDIKAN KARAKTER - Cahyadi, Ani (Analisis: Jurnal Studi Keislaman, 2014)
REVITALIZATION OF CHARACTER EDUCATION LEARNING:  This  article discusses  some  of the  issues  related to character  education  in Indonesia, ranging from the concepts and  Islamic  values  related  to  character education  to  learning patterns  that will be applied. This work concludes that Pancasila which becomes the core values in the formation of the Indonesian nation-state can be used as a reference in preparing the character education learning  program  and it,  by no mean, conflicts withIslamic  values.  By  using    elaborative-analysis  approach,    this study  offers  a number  of initial  concepts  that  can  be used  to revitalize  Pancasila  and  Religious Education  through  a multi- dimensional-based framework.